The synod 'with' young people (2018) paves the way for the synod on synodality (2023) - François Moog (Warszawskie Studia Teologiczne)
Pope Francis is very concerned to transform the Church through synodality. He has chosen the synod of bishops as the main tool for this reform. This paper shows how the functioning of the Synod of Bishops, which the pope has profoundly transformed, puts this project of a synodal Church into effect. From this point of view, the process of the 2018 synod on youth is an example of how synodality is transforming the Church. By taking the steps of this process step by step, the paper shows how the practice of synodality is deeply transforming the Church and how the synod of 2018 paves the way for the synod of 2023 on the synodality of the Church.